Prevention of the reasons intergenerational conflicts in families - L. M. Grishina (Вестник университета, 2021)
Conflicts within the family between representatives of different generations are considered in order to identify the most common causes and topics of conflicts between members of the same family, intergenerational relations in families. Families with representatives of three generation were interviewed: children, parents and grandparents. Questionnaires, surveys, and interviews were used to collect statistical data. Recommendations on forecasting, prevention and management of conflict situations within the family are given.